Evaluating participatory monitoring in mountainous tourist regions - Zeballos, Jazmin Campos; Valencia, Jefferson; Codalli, Fabia; Mitze, Fabian; Shagega, Frank; Weeser, Björn; Jacobs, Suzanne (Frontiers in Environmental Science, 2025)
In view of the considerable impact of climate change on water resources, it is crucial to promptly address the limited availability of consistent and reliable hydrometeorological data to enable timely decision-making. HydroCrowd employs a participatory monitoring approach to collect meteorological and hydrological data in vulnerable mountainous tourist areas. This paper presents an analysis of both non-frequent and regular volunteers who participated in the project, examines the motivation behind their participation, and evaluates the advantages and disadvantages of the project’s approach to data collection. The stations, smartphone application, and data collection process received, in general, a positive response. However, the lack of reliable internet connection in some regions hinders the observation upload process, which in turn hinders the participation of volunteers. The results suggest that such projects cannot solely rely on non-frequent volunteers, such as tourists. Communities and local stakeholders are instrumental in ensuring the continuous collection of data in a timely manner for projects of this nature.